Spectrophotometric Method for Determination of Fluoride Ion in Water Samples Based on its Bleaching Effect on Aluminium-SPADNS Lake - Mary Sukanya, C.; Himabindu, V.; Anjaneyulu, Y. (Asian Journal of Chemistry, 2016)
A simple and rapid spectrophotometric method for determining fluoride in potable water has been developed. The factors, which affect the bleaching effect of fluoride on the aluminium-SPADNS lake to adopt it as a spectrophotometric method for estimation of fluoride in water were studied. Beer’s law is obeyed from 0.0 to 4.0 ppm of fluoride ion buffered at pH 4.9 ± 0.03 at 590 nm. This method can be used over a wide concentration range of fluoride which is not possible in other spectrophotometric methods.